The witch's orchard : a novel - Sullivan, Archer (Minotaur Books, 2025)
"A ninth generation Appalachian herself, Archer Sullivan brings the mountains of North Carolina to life in The Witch's Orchard, a wonderfully atmospheric novel that introduces private investigator Annie Gore. Former Air Force Special Investigator Annie Gore joined the military right after high school to escape the fraught homelife of her childhood. Now, she's getting by as a private investigator and her latest case takes her to an Appalachian holler not unlike the one where she grew up. Ten years ago, three little girls went missing from their tiny mountain town. While one was returned, the others were never seen again. After all this time without answers, the brother of one of the girls wants to hire an outsider, and he wants Annie. While she may not be from his town, she gets mountain towns. Mountain people. Driving back into the hills for a case this old-it might be a fool's errand. But Annie needs to put money in the bank and she can't turn down a case. Not even one that dredges up her own painful past. In the shadow of the Blue Ridge, Annie begins to track the truth, navigating a decade's worth of secrets, folklore of witches and crows, and a whole town that prefers to forget. But while the case may have been buried, echoes of the past linger. And Annie's arrival stirs someone into action"-- Provided by publisher.